Effects of a home-based programme on physical activity among undergraduate female students in Iraq - Noori, Jian Abdullah; Soh, Kim Geok; Mohd Esa, Norhaizan; Ahmad Tarmizi, Rohani; Ahmed, Nabeel Abdulwahab (Human Resource Management Academic Research Society, 2017)
The study aimed to evaluate the effect of home-based programme to improve physical activity among undergraduate female students in Iraq. The participants were Iraqi sedentary undergraduate female students (N=44) who were assigned to two groups consisted of experimental group (N=22) and control group (N=22) respectively. The experimental group received a 12-week home based intervention programme which focuses on PA, while the control group were maintaining their usual life. Measurements for all the variables were taken prior to the intervention (pre-test), at week 6 (post-test1), and after 12 weeks (post-test2). The results of Mixed between-within subjects analysis of variance shows a statistically significant between the mean test scores in the pre-test, post-test1, and post-test2 measurements of PA in the experimental group. This study provided evidence that home-based intervention programme which focused on physical activity had a significant effect on improving physical activity.